2009
DOI: 10.1111/j.1751-1097.2008.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Survival and DNA Repair in Four Freshwater Cladoceran Daphnia Species Exposed to UV Radiation

Abstract: The biological responses of four freshwater daphniid species, Daphnia middendorffiana, D. pulicaria, D. pulex and D. parvula, to a single acute dose of ultraviolet B radiation (UVB) were compared. In addition to survival, we compared the induction of DNA damage (i.e. cyclobutane pyrimidine dimers) between species as well as the ability to repair this damage in the presence or absence of photoreactivating light. All four species showed high levels of shielding against DNA damage when compared to damage induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 38 publications
8
66
2
Order By: Relevance
“…Only the activity of the antioxidant enzyme catalase has been shown not to be thermally sensitive in response to UVR exposure in L. peronii tadpoles [72]. However, the DNA repair mechanisms of enzymatic photoreactivation (EPR) and nucleotide excision repair (NER) have been shown to increase with increasing temperature in ciliates [115], freshwater crustaceans [116], marine macroalgae [117], tobacco cells [118] and echinoid embryos [119], however, Connelly et al [120] found the opposite to be true in Daphnia. The photoprotective mechanism of ROS reduction by enzymatic antioxidant activity has also been found to be thermally sensitive in summer-caught mosquito fish Gambusia holbrooki exposed to UVR [39].…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Only the activity of the antioxidant enzyme catalase has been shown not to be thermally sensitive in response to UVR exposure in L. peronii tadpoles [72]. However, the DNA repair mechanisms of enzymatic photoreactivation (EPR) and nucleotide excision repair (NER) have been shown to increase with increasing temperature in ciliates [115], freshwater crustaceans [116], marine macroalgae [117], tobacco cells [118] and echinoid embryos [119], however, Connelly et al [120] found the opposite to be true in Daphnia. The photoprotective mechanism of ROS reduction by enzymatic antioxidant activity has also been found to be thermally sensitive in summer-caught mosquito fish Gambusia holbrooki exposed to UVR [39].…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…Kazerouni et al [39] found that the activities of superoxide dismutase and catalase were highest in fish acclimated to the average environmental temperature of 28°C, but was reduced in fish acclimated to lower and higher temperatures (18°C and 32°C). Importantly, the improved efficiency of EPR, NER and antioxidant activity due to changes in temperature has been found to reduce the negative effects associated with UVR exposure on development, survival, metabolic rate and locomotor performance [39,119,120]. Given that EPR, NER and antioxidant activity are thermally sensitive in other organisms, it seems likely that these physiological UVR defences are also thermally sensitive in amphibians.…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…Although PER is widespread taxonomically (16), its importance relative to dark repair is highly variable for different organisms. PER has been shown to be a particularly important mechanism of DNA repair in several species of amphibians (2), zooplankton (7,12,14), protists (26,31), and bacteria (22). Zenoff et al (39) found several strains of aquatic bacteria with various degrees of reliance on PER and no obvious use of NER, although Cytophaga sp.…”
Section: Discussionmentioning
confidence: 99%
“…An overall reduced metabolism at the cooler temperature could have contributed to these differences; however, it seems likely that the photolyase enzyme itself was less efficient at 15°C. The interaction of temperature with DNA repair is known for several other taxa exposed to UV-B, including a red alga, a ciliate, a rotifer, and several crustacean zooplankton species (7,13,21,26,36).…”
Section: Discussionmentioning
confidence: 99%
“…Marine and terrestrial organisms have adapted to prevent and cope with such UVR exposure and damage. These adaptations can be behavioral, such as moving into the shade (Gleason et al, 2006;Ma et al, 2013), physiological, such as absorptive pigmentation like melanin (Singaravelan et al, 2008) and mycosporine-like amino acids (MAAs) (Kuffner, 2002;Hylander and Hansson, 2013), or biochemical such as molecular repair (Carlson and Smith, 1981;Connelly et al, 2009) and antioxidants (Swindells and Rhodes, 2004;Hudelson, 2011).…”
Section: Introductionmentioning
confidence: 99%